2019
DOI: 10.18697/ajfand.85.17795
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumer knowledge, understanding and use of food and nutrition label information in the Tamale metropolis of Ghana

Abstract: The perception that consumers in low Income Countries have poor knowledge and understanding of food or nutrition labels and, therefore, do not rely on them at the point of purchase is rife. This study was aimed at assessing consumer knowledge and understanding and its influence on food label usage in the Tamale Metropolis of Ghana. An analytical cross-sectional study design was employed and mainly literate adults aged 15 to 60 years were conveniently selected and interviewed at various points-of-purchase inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Age, occupation, level of education, employment status, income, and marital status were positively associated with food label use (A. Aryee 2013; P. A. Aryee et al 2019;Osei, Lawer, and Aidoo 2012).. Other common factors reported in the studies that prompted consumers to use food labels were religious beliefs, food allergies, advertising, health claims, nutritional value, price, expiration date, use directions, storage information, and intolerance to certain foods. The reasons consumers gave for not using food labels were technical/scientific language, haste, small font sizes, a foreign language other than English, and time constraints (P. A.…”
Section: Predictors Of Food Label Use In Ghanamentioning
confidence: 97%
See 2 more Smart Citations
“…Age, occupation, level of education, employment status, income, and marital status were positively associated with food label use (A. Aryee 2013; P. A. Aryee et al 2019;Osei, Lawer, and Aidoo 2012).. Other common factors reported in the studies that prompted consumers to use food labels were religious beliefs, food allergies, advertising, health claims, nutritional value, price, expiration date, use directions, storage information, and intolerance to certain foods. The reasons consumers gave for not using food labels were technical/scientific language, haste, small font sizes, a foreign language other than English, and time constraints (P. A.…”
Section: Predictors Of Food Label Use In Ghanamentioning
confidence: 97%
“…Additionally, when respondents were asked about the frequency of use of food labels, the responses varied widely: about 52% said they do so 'always' in Tamale (P. A. Aryee et al 2019), 35.8% 'always' use the label in Accra (Aidoo 2016), 49.3% reported regular use in Koforidua (Darkwa 2014) and a national study among tertiary students reported that 31.3% use labels 'very often' (Madilo et al 2020). When purchasing a food product for the first time, only 37.2% used the label in Kumasi (Osei, Lawer, and Aidoo 2012).…”
Section: Consumer Use Of Food Labelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, ecolabels have received considerable attention in scholarly literature in the last decade. For instance, some studies focused on the impact of ecolabels on consumer behaviour (Brécard, Hlaimi, Lucas, 12 URL: www.onlinesciencepublishing.com | February, 2023 and use of ecolabels, although there are several studies on consumers' understanding and use of nutrition labels with varied findings though (Affram & Darkwa, 2015;Aryee et al, 2019;Osei, Lawer, & Aidoo, 2013). Hence, there is a need to understand whether consumers in Ghana, specifically students are aware of and use ecolabels in their purchasing decisions (Taufique, Siwar, Talib, Sarah, & Chamhuri, 2014;Testa, Iraldo, Vaccari, & Ferrari, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although food labels are mandatory but to understand the numerical display of food related information is a hindrance for consumer. Food processing organizations and policy makers have taken initiatives for designing food labels easy to understand for average consumers (Grunert, Wills & Fernandez-Selemin 2010;Aryee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%